ANALISIS PENGARUH PROFITABILITAS, KEBIJAKAN UTANG, DAN STRUKTUR ASET TERHADAP HARGA SERTA RETURN SAHAM DENGAN KUALITAS AUDIT SEBAGAI VARIABEL PEMODERASI - MF. Christinungrum; Aris Wibowo (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2017)
This research is intended to find out the effect of profitability (ROA), debt policy (DER) and assets structure on price and stock return with audit quality as a moderating variable. Samples of this research are consisted of 11 food and beverages companies from 2005-2013. The statistic regression result showed that profitability is significantly and positively affecting stock price, debt policy is not affecting stock price and assets structure significantly and negatively affecting stock price. Further statistical regression using moderating variable demonstrated that audit quality, which was represented by Big Four accounting firms, strengthened the correlation between profitability and stock price, while weakening the correlation between assets structure and stock price. The results on Model 3 also showed that profitability significantly and positively affect share returns while debt policy has a significantly and negatively effect on share return. Model 4 demonstrated that audit quality weakened the correlation between profitability and debt policy on share return.